Effect of Ascorbic Acid, Alpha-Tocopherol, Beta-Carotene and Total Polyphenol on Antioxidant Activity in Selected Malaysian Edible Plants - A.H, Zaibunnisa; Rohani K, Siti; Adillah A, Noor; M, Shahiza; A, Noorlaila (Malaysian Journal of Science, 2005)
Malaysian edible plants have played a significant role in maintaining human health. These usually associated with the presence of antioxidants like ascorbic acid, Î±-tocopherol, Î²-carotene and polyphenols in these plants. The objective of this study was to screen selected different types of Malaysian edible plants; tapioca shoots (Manihot utilissima), kesom (Polygonus minus), selom (Oenanthe javanica), mint (Mentha arrensis), cekur manis (Sauropus andrygonus) and ulam raja (Cosmos caudatus) for antioxidant compounds and relate it to its antioxidant activity. Î²-carotene and Î±-tocopherol were determined using hexane-ethyl-acetate extraction method while, ascorbic acid, total polyphenol and antioxidant activity were determined using titration, spectrophotometer and Î²-carotene bleaching method, respectively. Ulam raja, kesom, tapioca shoot and cekur manis contained significantly (p<0.05) the highest concentration of Î²-carotene (922.26mg/100g), total polyphenol (109.96 mg/100g), ascorbic acids (192.89 mg/100g) and Î±-tocopherol (19.23 mg/100g), respectively. However, kesom contained significantly the highest antioxidant activity (42.24%). Therefore, the presence of polyphenols in edible plants significantly increases its antioxidant activity properties when compared to the presence of other antioxidant compounds; Î²-carotene, ascorbic acid and Î±-tocopherol.